A Review on 2019-nCoV (SARS-CoV-2) in India - Mahawar, Pawan Kumar; Sharma, Abhay (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: The outbreak of the novel coronavirus, COVID-19, has been declared a pandemic by the WHO on March 11th of 2020. Novel Coronavirus infection mediated pandemic started in China in December 2019 and is still killing 1000s of people throughout the world. The second most populous country, India too is fighting against this infectious disease. The country is taking effective measures to curb the pandemic by exerting extensive campaigning on sanitation and strict social distancing measures to quell the explosion of the infection rate. Treatment: No drugs are currently approved for Coronavirus Disease-2019 (COVID-19), although some have been tried. In view of recent studies and discussion on tested drugs on COVID-19 patients of India, I aimed to review existing literature and relevant websites regarding these drugs used in India including allopathic, plasma therapy,Ayurvedic and homeopathic medication.